1999
DOI: 10.1103/physrevc.61.014306
|View full text |Cite
|
Sign up to set email alerts
|

Overlap functions in correlation methods and quasifree nucleon knockout from16O

Abstract: The cross sections of the (e, e ′ N ) and (γ, p) reactions on

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
62
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(68 citation statements)
references
References 69 publications
6
62
0
Order By: Relevance
“…This was confirmed in an exactly solvable many-body system in one dimension with a zerorange interaction [18]. The theorem was applied in [19] to obtain the overlap functions and spectroscopic factors from a model OBDM including Jastrow correlations, and later [20,21] applied to the calculation of cross sections for several reactions, such as (p, d), (e, e ′ p) and (γ, p). However, some problems with the numerical restoration procedure performed in [19], which is based on an exponential fit of the OBDM, were pointed out in [15], namely: i) the use of harmonic-oscillator single-particle wave functions, which do not have the correct exponential behavior in the asymptotic region, to construct the OBDM, and ii) the nature of the exponential fit allowed to obtain in [19] overlap functions for the unoccupied states, while in [15] it was demonstrated that such extraction is not possible starting from a CBF-type wave function.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…This was confirmed in an exactly solvable many-body system in one dimension with a zerorange interaction [18]. The theorem was applied in [19] to obtain the overlap functions and spectroscopic factors from a model OBDM including Jastrow correlations, and later [20,21] applied to the calculation of cross sections for several reactions, such as (p, d), (e, e ′ p) and (γ, p). However, some problems with the numerical restoration procedure performed in [19], which is based on an exponential fit of the OBDM, were pointed out in [15], namely: i) the use of harmonic-oscillator single-particle wave functions, which do not have the correct exponential behavior in the asymptotic region, to construct the OBDM, and ii) the nature of the exponential fit allowed to obtain in [19] overlap functions for the unoccupied states, while in [15] it was demonstrated that such extraction is not possible starting from a CBF-type wave function.…”
Section: Introductionmentioning
confidence: 93%
“…Recently Gaidorov et al [21] have presented results for the overlap functions of the p-shell in 16 O using a method similar to fit II. The procedure was applied to the correlated OBDM of [32] computed up to 11 fm, which uses the same shell model we are considering here, with similar energies and wave functions for the 1p 1/2 and 1p 3/2 .…”
Section: Exponential Decay Methodsmentioning
confidence: 99%
See 3 more Smart Citations